Phase-only shaped beam transmit-array - Cruz, Catarina C.; C. A. Fernandes; Matos, S.; Costa, J. R. (2018 IEEE International Symposium on Antennas and Propagation and USNC-URSI Radio Science Meeting, 2018)
A new analytical formulation is presented in this paper to obtain the phase correction function for planar transmitarrays, to produce a prescribed amplitude template. This phaseonly design enables using high transmission unit cells to favor maximum gain. Here, a transmit-array transforms the known power radiation pattern of the primary source into a desired output power pattern. As a proof of concept, two different output power radiation patterns are presented, namely, a sec2 with a roll-off at 45º and a flat-top with 20º of roll-off, at the 30 GHz Ka-band. The transmit-array aperture is 180 mm × 180 mm, with 60 mm focal length. It is illuminated by a 10.8 dBi feed radiation pattern, with circular polarization